The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsphotonics.2c00863
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency, Large-Area, Flexible Top-Emitting Quantum-Dot Light-Emitting Diode

Abstract: Flexible displays are essential to provide information in real time for human–machine interactions. As a next-generation display technology, quantum-dot light-emitting diodes (QLEDs) are potentially serving as key components for flexible displays. However, it is still challenging for QLEDs to simultaneously achieve flexibility, large-scale production, and high efficiencies. To this end, a strategy is proposed here by combining a top-emitting structure, optical microcavity optimization, and large-scale film pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…[225] Recently, Yu et al reported large-area top-emitting QLEDs (Figure 6e) prepared by combining surfactant-assisted blade-coating and vacuum evaporation processes. [229] Nonionic surfactant Tween 60 is introduced to achieve blade-coated ZnO and QD films on the Al-coated substrate. A flexible QLED with an active area of 400 mm 2 and EQE of 21.8% were fabricated with this approach (Figure 6f) as well as a 1.3-inch passive-matrix top-emitting QLED display by using patterned Ag cathode (Figure 6g,h).…”
Section: Spin Coating and Blade Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…[225] Recently, Yu et al reported large-area top-emitting QLEDs (Figure 6e) prepared by combining surfactant-assisted blade-coating and vacuum evaporation processes. [229] Nonionic surfactant Tween 60 is introduced to achieve blade-coated ZnO and QD films on the Al-coated substrate. A flexible QLED with an active area of 400 mm 2 and EQE of 21.8% were fabricated with this approach (Figure 6f) as well as a 1.3-inch passive-matrix top-emitting QLED display by using patterned Ag cathode (Figure 6g,h).…”
Section: Spin Coating and Blade Coatingmentioning
confidence: 99%
“…f) Images with a pattern, g) 19 × 19 passivematrix flexible top-emitting QLED display array, and h) EL image of Arabic numbers. (e-h) Reproduced with permission [229]. Copyright 2022, American Chemical Society.…”
mentioning
confidence: 99%
“…No substrate in the optical path may considerably improve the light outcoupling efficiency [ 89 , 90 , 91 ]. Also, a microcavity effect between two metallic electrodes can be utilized to tune the peak wavelength and enhance the color purity [ 92 , 93 , 94 , 95 ]. However, intense light emission in the normal direction results in a distorted angular profile of the Lambertian distribution, which may cause a poor viewing angle in display devices.…”
Section: Qled Frontplane Technologymentioning
confidence: 99%
“…Moreover, in terms of displays, the TE structure is more favorable because it allows a higher display aperture ratio and enables the devices to be integrated with opaque substrates such as Si wafers. [18][19][20][21] Optically, the QLEDs can be modeled as a cavity, in which light reflect back and forth by the bottom and the top electrodes. It is well known that there are two types of optical interferences in microcavity, namely wide-angle interference and multiple-beam interference.…”
Section: Introductionmentioning
confidence: 99%